The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ijc.30820
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the molecular basis of MSH2‐deficient tumors by combined germline and somatic analysis

Abstract: In a proportion of patients presenting mismatch repair (MMR)-deficient tumors, no germline MMR mutations are identified, the so-called Lynch-like syndrome (LLS). Recently, MMR-deficient tumors have been associated with germline mutations in POLE and MUTYH or double somatic MMR events. Our aim was to elucidate the molecular basis of MSH2-deficient LS-suspected cases using a comprehensive analysis of colorectal cancer (CRC)-associated genes at germline and somatic level. Fifty-eight probands harboring MSH2-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 40 publications
5
33
0
Order By: Relevance
“…Nevertheless, two pathogenic somatic variants affecting the two alleles of one MMR gene generally have the same effect. Several recent publications have shown that this is not uncommon in MSH2 and MSH6 negative tumors, particularly in the presence of an additional POLE or POLD1 variant or biallelic MUTYH variants . No two clearly pathogenic somatic MMR variants were found in any of the 11 tumors available for analysis in the present study.…”
Section: Discussionsupporting
confidence: 46%
“…Nevertheless, two pathogenic somatic variants affecting the two alleles of one MMR gene generally have the same effect. Several recent publications have shown that this is not uncommon in MSH2 and MSH6 negative tumors, particularly in the presence of an additional POLE or POLD1 variant or biallelic MUTYH variants . No two clearly pathogenic somatic MMR variants were found in any of the 11 tumors available for analysis in the present study.…”
Section: Discussionsupporting
confidence: 46%
“…Strikingly there was a somatic MSH6 M875I variant in the TNBC samples. The lack of MSH6 IHC staining is consistent with the presence of this likely pathogenic variant giving rise to a double negative MSI + tumor 13,14 . In contrast to MSH2 this variant was heterozygous suggesting that additional events such as epigenetic silencing may have contributed to the lack of MSH6 expression.…”
Section: Identification Of Pathogenic Ls Variantsupporting
confidence: 56%
“…In addition to MMR genes, most of the other PVs and likely PVs were detected in the MUTYH and GJB2 genes. Biallelic MUTYH variants have been detected in 1.8-3.1% of patients with LLS [20,21]. MUTYHassociated polyposis is extremely variable, ranging from severe polyposis coli to attenuated forms with a late age of onset or few adenomas, or CRC, which creates a phenotypic overlap with LS [20,22].…”
Section: Discussionmentioning
confidence: 99%